Pemanfaatan Teknologi Komunikasi Dalam Proses Uji Kenaikan Tingkat Pesilat Setia Hati Terate - Moch. Ichdah Asyarin Hayau Lailin; Ratnaningrum Zusyana Dewi (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of digital communication technology usage in the implementation of promotion tests on improving the performance quality of martial arts athletes at Persaudaraan SH Terate, Saradan Branch. Using a mixed-methods approach with an Explanatory Sequential design, the study began with quantitative data collection and analysis through Likert-scale questionnaires, followed by qualitative data enrichment via semi-structured interviews. The findings indicate that aspects such as digital media, communication, accessibility, assessment transparency, and organizational support significantly contribute to improved athlete performance. Linear regression analysis reveals that the use of digital testing has a positive and significant impact on performance quality. This is supported by qualitative data indicating increased motivation, efficiency, and perceptions of fairness in the evaluation process. Nonetheless, challenges such as limited device access and digital literacy remain barriers that need to be addressed. The study concludes that the integration of digital communication technology represents an innovative strategy in the transformation of performance development within martial arts organizations.